Improving Pedagogic Competence and Process Skills through Lesson Study Learning - Sukirno Sukirno; Hartutik Hartutik; Nursamsu Nursamsu (STAI Hubbulwathan Duri, 2021)
This research aims to improve pedagogic competence and process skills through lesson study learning. The qualitative descriptive method focuses on pedagogic competence and process skills through lesson study for teachers at an elementary school in Langsa. The type in this research is action research conducted in the classroom or School action research (School Action Research). The results of this study are; (1) the stages of the lesson study learning activity process with the average value obtained from the plan, do and see learning activities of 0.39% can be concluded to be good for implementation in learning activities; (2) the stages of teacher pedagogic competency assessment using the lesson study learning process with an average value of 0.64% is declared high, so it can be concluded that there is an increase in teacher pedagogic competence before and after; and (3) the stages of assessing process skills with an average value of 0.62% are declared good, meaning that it can be concluded that process skills before and after an increase occur.